Association of Pseudomonas and Serratia corneal ulcers with use of contaminated solutions. - Mayo, M S (1987)
The wetting and soaking solutions and contact lens cases of eye clinic patients commonly were contaminated with gram-negative bacteria during their use. Serratia marcescens occurred most frequently in preserved solutions, whereas Pseudomonas aeruginosa was most often recovered from home-prepared saline. The bacteria were recovered at densities of greater than 10(6) cells per ml and typically persisted in the solutions. Eight patients who developed bacterial keratitis during 1986 used solutions contaminated with the etiological agents of the infections. Improper hygienic practices of the patients and failure of some preservative systems were implicated in the development of the infections.